Current scenario of plant health clinics: Revamping to boost food security - SRIVASTAVA, M.P. (Indian Phytopathology, 2016)
Plant health clinics are primarily responsible for diagnosing plant ailments and providing remedial measure to reduce crop losses and improving food security. Globally pests and diseases cause enormous losses. It is believed that by saving 1% loss, millions of people can be fed. Today over one billion people are going hungry â€“ many of them are in rural areas. Plant clinics help to reduce crop losses and increase yield and improve lives. Plant clinics are all about plant health but they empower farmers with knowledge to enhance productivity. Global food security has received worldwide attention for the last 2 decades, in view of rising prices, changing climate, population explosion, urbanization and reduction of arable land, and massive losses in productivity due to plant pests. Over and above many diseases have caused catastrophe and made the situation still worst. Globally plant pests are responsible for 40% reduction in yield(Oerke, 2006). India monetarily looses INR 50,000 crores annually as per Assocham study (TOI, 2014). In most of the cases losses are due to lack of timely diagnostic- and appropriate advisory support. Wrong diagnoses by diagnostician or plant health personnel could prove suicidal. Global population is likely to reach 9.6 billion by 2050, while that of India is likely to reach 1.4 Billion equaling the population of China in 2028 and 1.7 billion by 2050. Population control is a difficult issue, and is only possible through political will and creating goodwill in public. Â Therefore it becomes imperative to increase production commensurate to the need of ever-growing population by revamping the working of plant clinics and empowering farmers with latest know-how and innovations on production technology and information/communication technology. Simultaneously diagnostic and management skill (thorough knowledge of pesticides/IPM) of diagnostician need to be improved. Empowering farmers with newer knowledge and technology and commitments to help growers may help to produce enough food meeting the need of of over 9 billion people, which is otherwise a tough job. Adoption of good scientifically ethical practices, advances in technology & innovations warrants to boost global and local food security. Success of plant clinics depends upon the diagnostic skill and effective communication electronically and telephonically using mobile phones. To make plant clinics more effective, Masters program in plant protection may be redesigned for those, who wish Â to Â choose career Â in plant clinic or an independent program in plant clinics can be initiated, like the ones we have in Florida.